Comparison between the Effect of Melatonin and Zinc sulfate in Prevention of cisplatin induced Nephrotoxicity in Rats - Adeeb A. Al-Zubaidy; Dalia Abd Al Kader Al-Salihy; Mustafa Ghazi Al-Abbassi (College of Pharmacy / Mustansiriyah University, 2012)
Cisplatin is an inorganic complex; the therapeutic effects of it are significantly improved by dose escalation. However high-dose therapy with cisplatin is limited by its cumulative nephrotoxicity and neurotoxicity. The aim of study was to compare between the effect of melatonin and zinc sulfate in prevention of cisplatin induced-nephrotoxicity in rats. Forty male albino rats weighing (200-250gm) were equally divided into four groups: normal group (0.2 ml isotonic saline group), control group "cisplatin group" (12 mg/kg cisplatin, single dose I.P.), melatonin group (15 mg/kg I.P.) prophylactically one day prior to cisplatin administration and continued for further 3 days, and zinc sulfate group (50 mg/ kg I.P.) prophylactically one day prior to cisplatin administration and continued for further 3 days. There was significant difference (p<0.05) between zinc sulfate and melatonin in reducing serum creatinine and BUN (melatonin more effective in reducing these parameters), and there was no significant difference (p>0.05) between them in reducing serum malondialdhyde (MDA) and increasing serum glutathione (GSH). As a conclusion, melatonin (15 mg/ kg I.P.) and zinc sulfate (50 mg/ kg I.P.) had protective effects against cisplatin- induced nephrotoxicity in rats. Melatonin was found to be more effective than zinc sulfate in its ability to reverse the abnormal renal function and preventing histopathological changes